88.2k views
5 votes
For f(x)=4x+1 and g(x)=x^-5, find (f+g)(x)

User Matveytn
by
5.3k points

2 Answers

4 votes

Answer:

x^(-5)+4x+1

given f(x)=4x+1 and g(x)=x^(-5)

Explanation:

f(x)=4x+1

g(x)=x^(-5)

(f+g)(x) means you are just going to do f(x)+g(x)

or (4x+1)+(x^(-5))

There are absolutely no like terms so it can't be simplified. We can use commutative and associative property to rearrange the expression.

x^(-5)+4x+1

User Gazareth
by
4.4k points
4 votes

ANSWER


(f + g)(x) = \frac{4{x}^(6) \: + {x}^(5) + 1 }{ {x}^(5) }

EXPLANATION

The given functions are:


f(x) = 4x + 1

and


g(x) = {x}^( - 5)

We now want to find


(f + g)(x)

We use this property of Algebraic functions.


(f + g)(x) = f(x) + g(x)

We substitute the functions to get:


(f + g)(x) = 4x + 1 + {x}^( - 5)

Writing as a positive index, we get:


(f + g)(x) = 4x + 1 + \frac{1}{ {x}^(5) }

The property we used to obtain the positive index is


{a}^( - n) = \frac{1}{ {a}^(n)}

We now collect LCD to get:


(f + g)(x) = \frac{4x \cdot {x}^(5) \: + {x}^(5) + 1 }{ {x}^(5) }

This simplifies to:


(f + g)(x) = \frac{4{x}^(6) \: + {x}^(5) + 1 }{ {x}^(5) }

User Nitin Labhishetty
by
4.5k points